Emodin repairs interstitial cells of Cajal damaged by cholelithiasis in the gallbladder - Huang, Zhen-peng; Qiu, Hu (Frontiers in Pharmacology, 2024)
Background: Hypercholesterolemia induces cholelithiasis and dysfunction of gallbladder motility. Interstitial cells of Cajal (ICCs) contribute to gallbladder motility. Emodin modulates the contractility of the gallbladder muscle; however, the underlying mechanism is unknown.Aim: This study aimed to explore the effects of emodin on gallbladder ICCs with cholelithiasis in a guinea pig model. Methods: Animals were randomly divided into a healthy control group and three study groups. All study groups received a high-cholesterol diet (HCD) for 8 weeks. Subsequently, they were randomly assigned to either the HCD group or one of the emodin treatment groups lasting 4 or 8 weeks. Total cholesterol (TC) and triglyceride (TG) were measured to determine changes in serum lipid levels.Immunohistochemistry was performed to detect the morphology and number of ICCs.TUNEL assays were performed to detect ICC apoptosis. Transmission electron microscopy was employed to observe ICC structure. Western blotting and real-time polymerase chain reaction were used to detect changes in stem cell factor (SCF)/c-kit pathway expression.Results: Serum TC and TG were higher in all study groups. In cases of cholelithiasis, SCF/c-kit pathway was downregulated, the number of gallbladder ICCs were decreased, apoptosis was increased, and the ICCs network structure was damaged. After emodin treatment, SCF/c-kit pathway upregulated, the number of gallbladder ICC increased, apoptosis decreased, and the ICCs network structure recovered.Cholelithiasis downregulates SCF/c-kit pathway and damages gallbladder ICCs. Emodin upregulates SCF/c-kit pathway and increases gallbladder ICCs, contributing to recovery from gallbladder motility disorders.